'If I want safe food I have to grow it myself': Patterns and motivations of urban agriculture in a small city in Vietnam's northern borderlands. (July 2020) - Pham, Thi-Thanh-Hiên; Turner, Sarah
Highlights: Food gardening is found in all sectors of the small upland Vietnam city of Lào Cai, with a diversity of forms and size. In all cases gardeners seldom have formal land-use rights and must negotiate access. Access to 'safe and clean' vegetables is the prime motivation for gardening, rather than basic food needs. Other important motivations include economic gains (with nuances), health, and social interactions. More Global South case studies of urban agriculture in small cities are needed to further advance our understandings of garden structures and spatial variations, farmer motivations, and state-gardener relations. Abstract: Urban agriculture literature regarding the Global South reveals important knowledge gaps concerning spatial variations of food gardens across cityscapes, gardener motivations, and tensions with urban planning regulations, especially in locales beyond sub-Saharan Africa. In Vietnam, urban agriculture is growing in popularity and gaining media attention but there is little research as to why urban agriculture is practiced in smaller Vietnamese cities, especially those close to rural hinterlands. In this paper we investigate small-scale urban agriculture – or food gardens – in Lào Cai, a small upland city located on the Sino-Vietnamese border. We find a complex diversity of garden sizes and land management arrangements where gardens are built, including on state institutional land, thanks to informal arrangements. Gardener motivations focus predominantly on food safety concerns, contrasting with key motivations found elsewhere in the Global South. Throughout the city, albeit more so in newly urbanising sectors, this urban practice remains precarious due to irregular land access and confusing city authority regulations. We thus examine how urban residents are working to access safe food and contribute to their city's urban food system while state officials tend to focus their priorities elsewhere.